2020
DOI: 10.1186/s12879-020-05035-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, antimicrobial susceptibility patterns, serotypes and risk factors for group B streptococcus rectovaginal isolates among pregnant women at Kenyatta National Hospital, Kenya; a cross-sectional study

Abstract: Background: Estimates of Group B Streptococcus (GBS) disease burden, antimicrobial susceptibility, and serotypes in pregnant women are limited for many resource-limited countries including Kenya. These data are required to inform recommendations for prophylaxis and treatment of infections due to GBS. Methods: We evaluated the prevalence, antimicrobial susceptibility patterns, serotypes, and risk factors associated with rectovaginal GBS colonization among pregnant women receiving antenatal care at Kenyatta Nati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 19 publications
2
13
5
Order By: Relevance
“…On the other hand, El Aila et al 45 and Jisuei et al 66 detected reduced sensitivity of the isolates to vancomycin (76% and 80% respectively). In our study, GBS was 100% sensitive to levofloxacin.…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, El Aila et al 45 and Jisuei et al 66 detected reduced sensitivity of the isolates to vancomycin (76% and 80% respectively). In our study, GBS was 100% sensitive to levofloxacin.…”
Section: Discussionmentioning
confidence: 94%
“…However, antibiotic resistance is not restricted to ST-17 or other emerging hypervirulent complexes. Reduced sensitivity to many antibiotics, including penicillin G, ampicillin, clindamycin, and vancomycin has been detected in GBS-colonized pregnant women in Kenya, China, Ethiopia, South Korea, Brazil, Poland, and the United States ( Lu et al, 2014 ; Yoon et al, 2015 ; Mengist et al, 2017 ; Burcham et al, 2019 ; do Nascimento et al, 2019 ; Jisuvei et al, 2020 ; Kaminska et al, 2020 ). Erythromycin and clindamycin resistance have been observed in adult patients in a Taiwanese hospital ( Tsai et al, 2019 ), while penicillin and multidrug-resistant GBS were noted at multiple hospitals in Japan ( Nagano et al, 2012 , 2019 ).…”
Section: Clinical Outcomes and Risk Factors Associated With Early-ons...mentioning
confidence: 99%
“…Unfortunately, a trivalent vaccine still does not include all clinically-relevant serotypes and could lead to selection of nonvaccine strains through capsule switching, a phenomenon that has been observed in many high-risk populations and among ST-17 strains (Bellais et al, 2012;Meehan et al, 2014;Neemuchwala et al, 2016;Nagano et al, 2019). Further, a recent study identified patients that were co-infected by multiple GBS serotypes at once (Jisuvei et al, 2020), which may enable capsule switching. Thus, a hexavalent CPS conjugate vaccine derived from serotypes Ia, Ib, II, III, IV, and V would cover more clinically-relevant strains (Bianchi-Jassir et al, 2020).…”
Section: Gbs Serotypes and Capsule Polysaccharide-based Vaccinesmentioning
confidence: 99%